2023
DOI: 10.3390/s23031300
|View full text |Cite
|
Sign up to set email alerts
|

Risk Field of Rock Instability using Microseismic Monitoringdata in Deep Mining

Abstract: With the gradual depletion of surface resources, rock instability caused by deep high stressand mining disturbance seriously affects safe mining. To create effective risk management, a rockinstability risk field model using microseismic monitoring data is proposed in this study. Rockinstability risk was presented visually in 3D visualization. The in-situ microseismic monitoringdata was collected and analyzed to make calculation of peak ground velocity (PGV), peak groundacceleration (PGA), energy flux, energy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…By continuously monitoring changes in the underground rock mass and providing real-time data on ground pressure, microseismic monitoring technology empowers mine management with the ability to provide early warnings and predictions for ground pressure. This contributes to strengthening mine safety measures, reducing the risk of accidents caused by ground pressure, and ensuring the safety of miners [4].…”
Section: Ground Pressure Monitoring and Predictionmentioning
confidence: 99%
“…By continuously monitoring changes in the underground rock mass and providing real-time data on ground pressure, microseismic monitoring technology empowers mine management with the ability to provide early warnings and predictions for ground pressure. This contributes to strengthening mine safety measures, reducing the risk of accidents caused by ground pressure, and ensuring the safety of miners [4].…”
Section: Ground Pressure Monitoring and Predictionmentioning
confidence: 99%
“…With the continuous growth in the demand for deep underground resource development, vertical shaft depths have exceeded 1500m, leading to increasingly prominent challenges in deep geological conditions [1][2][3][4] . By comparing the core samples from engineering exploration boreholes(figure 1), it is observed that shallow formations have relatively low stress levels, resulting in intact core samples with fewer joint fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Dong LJ [ 32 ] uses traveltime tomography to early identify abnormal areas of complex rock mass geological structures and better predict potential risks in roadways. In addition, he also applies microseismic data and acoustic emission technology to disaster prediction [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%